Radon doses in the indoor environments of Murree and Islamabad, Pakistan: A comparison of active and passive techniques. Issue 6 (October 2016) - Ali, Nawab; Muhammad, Wazir; Khattak, Nimat U.; Khan, Ehsan U.; Rajput, Muhammad U.; Akram, Muhammad; Hussain, Safeer; Mujahid, Shafiq A.
To study the radiological impact of indoor radon levels in different seasons on population, indoor air samples were collected from Islamabad (Alt. 534 m) and Murree (Alt. 2300 m) regions. Radon concentrations were measured using an active technique by taking in situ measurements on RAD-7, solid state α-detector and passive technique by taking time integrated measurements on CR-39 detector, in winter, spring, summer and autumn. The results of both techniques were analysed and compared. The suitability of active technique is discussed. Both active and passive measurement techniques lead to annual mean effective doses of (3.12, 1.28) mSva −1 and (3.23, 1.15) mSva −1, respectively to the inhabitants of respective regions and a strong correlation has been observed between the results of both techniques. The results showed that population residing in Murree region received comparatively less doses as compared to population in Islamabad region. Furthermore, the estimated dose levels for both regions were found within the annual dose limits recommended by the International Commission on Radiological Protection.